Предмет: Математика,
автор: 20Данил04
Упростите выражение (-0,3x-0,4y)*4-3(-2,4x-1,2y) и найдите его значение, если x=0,2 и y=-0,1
Ответы
Автор ответа:
0
-1,2х-1,6у+7,2х=3,6у=-1,2х(1-6)-1,6у(1-2,25)=-1,2х*(-5)-1,6у*(-2,25)=6х+2у=6*0,2+28(-0,1)=1,2-0,2=1
Автор ответа:
0
(-0.3x-0.4y)*4-3(-2,4x-1,2y) =
-1.2x-1,6y+7,2x+3,6y=
6x+2y=
6*0,2+2*(-0,1)=1,2-0,2=1
Вроди как так :)
Похожие вопросы
Предмет: Физика,
автор: Plusznania
Предмет: Физкультура и спорт,
автор: dfdffeaed
Предмет: Алгебра,
автор: zds19042007
Предмет: Математика,
автор: zhamilyaalmasovna
Предмет: Биология,
автор: sashagoncharova